Q. 134.3( 3 Votes )

Using factor theo

Let, f (y) = 2y3-5y2-19y+42

The factors of the constant term + 42 are

Putting y = 2, we have

f (2) = 2 (2)3 – 5 (2)2 – 19 (2) + 42

= 16 – 20 - 38 + 42

= 0

So, (y - 2) is a factor of f (y)

Let us now divide

f (y) = 2y3-5y2-19y+42 by (y - 2) to get the other factors of f (x)

Using long division method, we get

2y3-5y2-19y+42 = (y - 2) (2y2 – y – 21)

2y2 – y - 21 = (y + 3) (2y – 7)

Hence, 2y3-5y2-19y+42 = (y - 2) (2y - 7) (y + 3)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics